PENGEMBANGAN APLIKASI ODOO DENGAN COMMAND LINE INTERFACE TERHADAP WAREHOUSE MANAGEMENT SYSTEM MENGGUNAKAN MODEL EXTREME PROGRAMMING: STUDI KASUS: PT INDOGUNA UTAMA - Elis Sondang Dasawati; Brosky Samson Putra Halim (Jurnal Informatika dan Bisnis, 2019)
In the ongoing system, ERP Odoo has been used. However, the data input process become longer. This data input process based on GUI (Graphical User Interface). Interaction that occurs between user and computer is very much, thus slowing the input process. Therefore, a CLI-based system (Command Line Interface) is made to receives the main input in the form of barcode.In the system that has been created, researcher uses weight information that contained in the LOT code. User only have to scan LOT code using barcode scanner device, and system will process the data.The CLI-based system make the data input process become faster, because the weight of goods information already contained in the LOT code. User only need to input the LOT code and the system will convert it to weight for each box. Keyword: Command Line Interface, Warehouse Management System, Enterprise Resource Planning, Extreme Programming.